2018
DOI: 10.3233/bsi-180179
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal diffusion, spatial distribution and physical state of a potential anticancer drug in mouse skin as studied by diffusion and spectroscopic techniques

Abstract: Understanding the efficiency of a transdermal medical drug requires the characterization of its diffusion process, including its diffusion rate, pathways and physical state. The aim of this work is to develop a strategy to achieve this goal. FTIR spectroscopic imaging in conjunction with a Franz cell and HPLC measurements were used to examine the transdermal penetration of deuterated tert-butyl phenylchloroethylurea (tBCEU), a molecule with a potential anticancer action. tBCEU has been solubilized in an expedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Figure a presents the absorbance of typical tissues such as the liver, cornea, cartilage, and dermis in the wavelength range spanning from 2.5 to 10.5 µm, which are taken from the literature. [ 22 25 ] (Liver, cornea, sclera, articular cartilage, and dermis tissues have similar FTIR spectra, as shown in Figure S1, Supporting Information) It is revealed that the strongest absorption is at 6.1 µm which coincides with both the amide‐I resonance and the bending mode of water. On the short wavelength side, the main OH‐stretch mode of water is located at ≈3 µm.…”
Section: The Tabletop Mir Fs Laser Tissue Ablation Platformmentioning
confidence: 90%
“…Figure a presents the absorbance of typical tissues such as the liver, cornea, cartilage, and dermis in the wavelength range spanning from 2.5 to 10.5 µm, which are taken from the literature. [ 22 25 ] (Liver, cornea, sclera, articular cartilage, and dermis tissues have similar FTIR spectra, as shown in Figure S1, Supporting Information) It is revealed that the strongest absorption is at 6.1 µm which coincides with both the amide‐I resonance and the bending mode of water. On the short wavelength side, the main OH‐stretch mode of water is located at ≈3 µm.…”
Section: The Tabletop Mir Fs Laser Tissue Ablation Platformmentioning
confidence: 90%